Pakaian Tradisional Melayu Sebagai Representasi Identitas Budaya - Arbi, Arbi; Pesona, Melda Darys; Nersa, Mutiara; Amanah, Istifarizah; Fauziah, Lili; Lestari, Lena Bunga (Universitas Nurul Jadid, 2025)
Malay clothing represents a rich cultural heritage filled with symbolic meanings, embodying the values of tradition, religion, and social identity of the Malay community. More than just attire, it reflects philosophy of life, morality, and aesthetics passed down through generations. This study aims to explore the meanings, functions, and types of traditional Malay clothing within the social and cultural context of the Malay society, particularly in regions such as Riau, Indonesia. The research employs a library research method by collecting and analyzing data from various literature sources including books, journals, and scientific articles. The findings reveal that Malay clothing carries deep symbolic meanings such as modesty, dignity, and adherence to Islamic teachings. Its functions include spiritual, physical, customary, aesthetic, cultural, social, and religious roles. Malay clothing is also categorized based on its usage context, such as daily wear, semi-formal, formal, religious attire, and wedding costumes. This study underscores the importance of preserving traditional clothing as a cultural heritage and a symbol of the Malay identity